The Conflict of Values and Its Impact on Cultural and Social Integration between Jews of the crossing and Kibbutz Residents: A Study of the Novel( Scapegoat) by the Iraqi Jewish Author Eli Amir - Assi dr. Raad Hassan Ali Al-Attabi (Journal of College of Education, 2025)
The phenomenon of value conflict is one experienced by most societies, particularly those that receive immigrants and newcomers. This phenomenon is inherently tied to life in any society and manifests at all levels of social existence, in social phenomena such as role conflicts or social relationships. Moreover, it significantly impacts the issue of cultural and social integration. This study explores the theme of value conflict between Jews of the crossing and kibbutz residents during the 1950s, shortly after the establishment of the “Hebrew state” in occupied Palestine, where two distinct cultures met: the Eastern-oriented culture of Jews of the crossing and the Western-oriented culture of kibbutz dwellers. The novel Scapegoat by Jewish author Eli Amir reflects the challenges of adaptation and integration into kibbutz society, despite the protagonist Nuri’s considerable efforts to assimilate into this new community Ultimately, all his attempts end in failure.
Keywords: Value conflict, cultural and social integration, The crossing, kibbutz residents, Scapegoat .